Germany : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
Increases in core inflation owing to the VAT hike were smaller than expected, initially constituting a puzzle and leading to speculation about delayed increases or competitive pressures. Given Germany's large size and openness, spillover interactions appear to have increased over time. In the midst of a strong recovery, Germany is facing shortages of labor, the emigration of high-skilled labor, and a reduction in immigration. Germany's traditionally insider-dominated corporate governance system has undergone substantial reforms, leading to a pronounced strengthening of control by outsiders.